Synthesis of Silver-Doxycycline Complex Nanoparticles and Their Biological Evaluation on MCF-7 Cell Line of the Breast Cancer - Vahid Mohammadkarimi; Negar Azarpira; Zahra Ghanbarinasab; Pezhman Shiri; Fatemeh Sadat Dehghani; Amin Nakhostin-Ansari; Fatemeh Tayyebi-Khorrami; Amir Atapour; Ali Mohammad Amani (Journal of Chemistry)
In the current study, we aim to evaluate the effect of the combination of silver and doxycycline (silver-doxycycline complex) on the viability of the MCF-7 cell line of the breast in comparison with each of them. The Ag-doxycycline NPs were synthesized using silver nitrate and doxycycline solutions. The synthesized Ag-doxycycline NPs were characterized with several analyses. Ag-doxycycline NPs with a concentration of 25 μM is significantly more effective in decreasing the viability of MCF-7 cells than Ag with the same concentration (P<0.05). Doxycycline with a concentration of 6.25 μM also has a more potent effect on the viability of MCF-7 cells than Ag with the same concentration (P<0.05). Ag-doxycycline NPs with a 25 μM concentration is more effective than the concentration of 3.125 μM (P<0.05). Ag-doxycycline NPs were found to be more effective than AgNPs alone in inhibiting the growth of the MCF-7 cells. Also, the increasing utility of nanotechnology in multiple aspects of medicine can lead to using this technology in the treatment of different types of cancer in the future.